Management of Postherpetic Neuralgia with Pulsed Radiofrequency Dorsal Root Ganglion: A Case Report - Muh Dahlan; Alamsyah Ambo Ala Husain (HM Publisher, 2023)
Introduction: Radiofrequency therapy is a minimally invasive procedure that has been used for about three decades to treat various chronic pain, such as postherpetic pain. This case study aims to describe the use of PRF in postherpetic neuralgia. Case presentation: A woman, 71 years old, came with complaints of right low back pain. Pain that is felt like burning, burning, sometimes pain feels like being stabbed, electrocuted, throbbing, and the pain will increase if the area of the skin is touched by a cloth. The pain began to be felt approximately 11 years ago. Physical examination shows vital signs; blood pressure 140/75 mmHg, pulse 76x/minute, respiratory rate 20x/minute, oxygen saturation 97%, temperature 36,5oC, numeric rating scale (NRS) 8-9/10. On examination of the right lumbar region, hypopigmented lesions appeared around the right waist at L3, L4, and L5 levels. No hyperemia and edema were found, and no obvious sensory loss. Assessment of pain score according to the Socrates method 8/10, S-LANSS score (self-report Leeds assessment of neuropathic symptoms and signs) 16. The patient has been diagnosed with postherpetic neuralgia. Patients were treated with a pulsed radiofrequency (PRF) procedure on the dorsal root ganglion (DRG). Pulsed radiofrequency was performed on the dorsal root ganglion at L1, L2, L3, and L4 levels. Concussion: The pulsed radiofrequency procedure on the dorsal root ganglion is a minimally invasive procedure that is effective and safe in treating postherpetic neuralgia pain. The use of imaging guidance in this procedure can improve the accuracy of needle tip placement and prevent side effects and complications.